THE CONCEPT OF MASCULINITY SYMBOL WITHIN AMERICAN SOCIETYÃ¢â‚¬â„¢S PERSPECTIVE AS PORTRAYEDINÃ¢â‚¬Å“THE MORTAL INSTUMENTS: CITY OF BONESÃ¢â‚¬Â - Ningrum, Amila Sholehati (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2015)
This study is about concept of masculinity symbol in Cassandra Clare’s work entitled The Mortal Instruments: City of Bones. Masculinity concept as portrayed in the novel is closely related to the superiority of alpha male, represented in the characterization of Shadowhunter. This concept then is being related to the portrayal of the Shadowhunters society in which the story set. This study employs masculinity theory, semiotics, and sociological approach. Semiotics theory is applied to find out symbols of masculinity concept. In addition, sociological approach is conducted to describe the masculinity concept shaped within the society in the novel as reflecting American society. The result of the study shows that masculinity concept has symbols in Shadowhunter life in form of characters, object, weapon, and male’s action. Meanwhile, the masculinity phenomena, such as homosexual, army membership, and guardian job exist as trends which are popular in certain period of time in American modern society.